Exploring the consistency of the SF-6D - Ferreira, Lara Noronha (2018)
Objective: The six dimensional health state short form (SF-6D) was designed to be derived from the short-form 36 health survey (SF-36). The purpose of this research was to compare the SF-6D index values generated from the SF 36 (SF-6D(SF-36)) with those obtained from the SF-6D administered as an independent instrument (SF-6D(Ind)). The goal was to assess the consistency of respondents answers to these two methods of deriving the SF-6D. Methods: Data were obtained from a sample of the Portuguese population (n = 414). Agreement between the instruments was assessed on the basis of a descriptive system and their indexes. The analysis of the descriptive system was performed by using a global consistency index and an identically classified index. Agreement was also explored by using correlation coefficients. Parametric tests were used to identify differences between the indexes. Regression models were estimated to understand the relationship between them. Results: The SF-6D(Ind) generates higher values than does the SF-6D(SF-36), There were significant differences between the indexes across sociodemographic groups. There was a significant ceiling effect in the SF-6D(Ind) a but not in the SF-6D(SF-36). The correlation between the indexes was high but less than what was anticipated. The global consistency index identified the dimensions with larger differences. Considerable differences were found in two dimensions, possibly as a result of different item contexts. Further research is needed to fully understand the role of the different layouts and the length of the questionnaires in the respondents' answers. Conclusions: The results show that as the SF-6D was designed to derive utilities from the SF-36 it should be used in this way and not as an independent instrument.